Balloon pulmonary angioplasty in patients with chronic thromboembolic pulmonary hypertension: short- and long-term results from a cohort in Brazil - Fabio Solano de Freitas Souza; Marcelo Gottschald Ferreira; Iury Andrade Melo; Marta Ferreira Leite de Sá; Camila Melo Coelho Loureiro; Rosalvo Abreu; Paulo Henrique Alves de Carvalho; Mateus dos Santos Viana; Valdemar Oliveira Jr; Luiz Eduardo Fonteles Ritt (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: A significant number of patients with chronic thromboembolic pulmonary hypertension (CTEPH) are not eligible for pulmonary endarterectomy and may be treated with balloon pulmonary angioplasty (BPA). Although BPA programs have recently been developed in Brazil, no results have yet been published. The objective of this study was to assess the clinical and hemodynamic progression of the first patients treated with BPA at our center. Methods: This was an observational study of 23 patients with CTEPH enrolled in the BPA program of a specialized center in Brazil between 2015 and 2020. Results: After a mean of 5.6 ± 1.3 sessions and 11 ± 2.8 treated segments/patient (at a mean of 6.7 ± 2.9 months post-BPA), there was a 26% decrease in mean pulmonary artery pressure (51 ± 11 vs. 38 ± 11 mmHg; p < 0.0001), a 43% decrease in pulmonary vascular resistance (10 ± 3.7 vs. 5.7 ± 3.3 WU; p < 0.0001), and a 22.5% increase in the cardiac index (2.38 ± 0.6 vs. 2.95 ± 0.6 L/min/m2; p < 0.0001). There was an increase in the six-minute walk distance and an improvement in functional class. Acute lung injury with clinical manifestations was observed after 7% of the BPA sessions. None of the patients required intubation. During a mean outpatient follow-up period of 38 ± 22 months, two patients were referred for additional BPA sessions due to clinical worsening and new hospitalizations. Two deaths were recorded (due to CTEPH progression and gastrointestinal bleeding, respectively). Conclusions: Among this first group of patients treated with BPA in Brazil, there was significant short- and long-term clinical improvement, together with a low frequency of complications.